2013
DOI: 10.1155/2013/456352
|View full text |Cite
|
Sign up to set email alerts
|

Parasitic Infections: A Role for C-Type Lectins Receptors

Abstract: Antigen-presenting cells (APCs) sense the microenvironment through several types of receptors that recognize pathogen-associated molecular patterns. In particular, C-type lectins receptors (CLRs), which are expressed by distinct subsets of dendritic cells (DCs) and macrophages (MØs), recognize and internalize specific carbohydrate antigens in a Ca2+-dependent manner. The targeting of these receptors is becoming an efficient strategy for parasite recognition. However, relatively little is known about how CLRs a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
40
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 88 publications
3
40
0
Order By: Relevance
“…This observation is in line with previous reports from other T. cruzi strains which demonstrated that this parasite displays highly glycosylated membrane proteins related to the invasion of host cells through recognition by CLRs 31, 54, mainly DEC205 and SIGN 18, 55. However, the role of CLRs in vivo has not been determined.…”
Section: Discussionsupporting
confidence: 88%
“…This observation is in line with previous reports from other T. cruzi strains which demonstrated that this parasite displays highly glycosylated membrane proteins related to the invasion of host cells through recognition by CLRs 31, 54, mainly DEC205 and SIGN 18, 55. However, the role of CLRs in vivo has not been determined.…”
Section: Discussionsupporting
confidence: 88%
“…Parasitic nematodes exploit lectin receptors to evade the host immune response by secreting C-type lectins (Loukas and Maizels, 2000, Vazquez-Mendoza et al., 2013). However, very little is known about clec-1 .…”
Section: Discussionmentioning
confidence: 99%
“…C-type lectin-like receptors sense SCPs from various kinds of pathogens, such as parasites (60), fungi (8, 61), bacteria, and viruses (62, 63) consist of more than 1000 members (60, 64). The number of extracellular carbohydrate recognition domain (CRD) and their cellular localization classifies CLRs to type-I transmembrane, type-II transmembrane, and soluble CLRs (65); where type-I CLRs contain multiple CRD and type-II CLRs contains single CRD (66).…”
Section: Sensing Of Scps By Prrsmentioning
confidence: 99%